Legal Vacancies in the Transfer of Rights to Class III State Houses in the Form of Flats - Jatmika, Adi (Universitas PGRI Madiun, 2021)
Class III state houses are in the form of flats including those whose rights can be transferred either independently and / or in the form of Apartment Units with or without their land by means of leasing, there are sectoral regulations that regulate these matters such as rules regarding state houses, flats, state property, and land registration have the impact of disharmony and legal vacancies. The research method used is the juridical-normative research method. The final part of this research concludes that the validity of Class III State Houses in the Form of Flats must meet the requirements stipulated in statutory regulations, including the status of land rights, the distribution of apartment elements such as shared land, shared objects, and parts together as regulated in the Law on Flats, the existence of the Association of Owners and Occupants of Apartment Units (PPPSRS) which is formed by the agency concerned, as well as the issuance of the Occupancy Permit of Class III State Houses in the Form of Flats. Holders of occupancy permits have rights, namely SIP Holders of State Houses of Category III can apply for transfer of Class III State Houses to the relevant Minister, protection of efforts to apply for transfer of these rights is preventive based on positive law in Indonesia which regulates the transfer can be carried out. There was a vacuum and disharmony in the Legislation regarding the Transfer of Rights to Group III State Houses in the Form of Flats, seen from the existence of Regulations that govern the transfer as in Presidential Regulation Number 11 of 2008, on the other hand there are no regulations governing the transfer of Class III State Houses. In the form of a Flat with the implications regarding the status of the Flat Ownership Unit (SHM Sarusun) as well as the status of joint shares, common objects, and common land, whether it can be transferred and managed by the Association of Owners and Residents of Flats (PPPSRS) or still become State Property